The Eurasian Economic Union: Today and Tomorrow - M. V. Myasnikovich (Мир новой экономики)
The Eurasian Economic Union States should strengthen their sovereignty within the EAEU through the complementary specialization of economies, cooperative ties in knowledge-intensive industries and economic sectors around the entire economic cycle. However, the Eurasian integration needs a new impetus. The period having passed since the EAEU creation imposed a necessity to qualitatively revise what has been done, to frankly state that a whole range of the Treaty’s provisions was not fulfilled as well as to formulate and propose specific mechanisms for further implementation of its provisions, to outline new integration horizons, to adopt appropriate decisions and to start acting. The article provides an idea of where the Eurasian integration is currently moving. It offers an overview of the Strategic Directions for Developing the Eurasian Economic Integration until 2025, the document that embodies the transition from the shaping stage (2015–2019) to the project integration stage (2020–2025). The new stage’s essence is about ensuring conditions for the specific joint economic projects at both interstate and individual economic entity level. The article mentions what has already been accomplished in this direction and what lies ahead. It reflects the integration’s impact on the participating countries’ economies: both existing and forecast one. Furthermore, it touches upon the issue of dedollarizing the Union countries’ mutual trade, digitalization, the EAEU international cooperation as well as global economic risks and ways to overcome those through integration cooperation. In conclusion, the article proposes new principles of the integration association’s work.